The Influence of Sucrose on Biomass and Glycosides Content of Callus Cultured from the Leaves of Stevia rebaudiana Bertoni - Obaid, Lara M.; Abdulhalem, Ansam G. (Iraqi Journal of Science, 2024)
Stevia rebaudiana Bertoni contains diterpenoid steviol glycosides that have no adverse impact on blood sugar levels despite being 300 times sweeter than sugar. This study aimed to investigate the rate of callus induction from stevia leaves and the content of glycosides when changing the sucrose percentage in the culture medium.. Murashige and Skoog (MS) culture medium supported by 4.0 mg/l naphthalene acetic acid (NAA) and 1.0 mg/l benzyl adenine (BA) was used,  and different concentrations of sucrose (2, 3, 4, 5  and 6%) were tested .The extraction of glycosides from leaf and callus tissues was performed by using methanol. Extracted glycosides were analyzed by high-performance liquid chromatography (HPLC). The results showed significant influences of sucrose on callus initiation. The concentration of 3% sucrose had the highest fresh and dry weight. No callus was induced in the MS medium with a high concentration of sucrose (5% and 6%). However, the highest  glycoside content, stevioside and rebaudioside were obtained from callus treated with 4% concentration followed by 3% sucrose the treatment . The highest fresh and dry weight average was obtained with a 3% concentration of sucrose, this treatment also increased the concentration of glycosides in the callus twice as much as in the leaves, and concentrations of 3% and 4% of sucrose gave very similar concentrations of glycosides in callus in terms of being double what was found in the leaves something which may aid in the development of a stevia glycosides based industry.